Influence of Work Duration on Helminthiasis in Pig Farmers in Tabanan - Sri Idayani; Ni Kadek Sylvia Amanda; Anak Agung Ayu Eka Cahyani (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Helminthiasis is a group of diseases caused by parasitic worms that remains a persistent public health challenge in Indonesia, with the heaviest burden borne by agricultural communities. Due to frequent exposure to contaminated environments, pig farming poses a high risk for parasitic infection, including those caused by nematodes. Methods: A cross-sectional performed in 30 pig farmers from Bongan Village, Tabanan. Data were collected through laboratory examination of fecal samples and structured interviews using questionnaires. A descriptive analysis was conducted, followed by Fisher's Exact Test to assess the association between work duration and helminthiasis. Result: Proportion of helminthiasis was 10% (3 of 30 respondents). Three respondents tested positive for helminthiasis (two respondents tested positive for the eggs of Taenia Sp, one respondent tested positive for the eggs of Ascaris lumbricoides). The result of bivariate analysis showed an increased risk of helminthiasis in the group with more than 35 years of work duration (POR: 16.1; 95% CI: 1.8—145.3, p-value: 0.032) compared with those with 35 years or less. Fisher's Exact Test indicated a statistically significant association between work duration and helminthiasis. Conclusion: Proportion of helminthiasis was 10%. Two respondents tested positive for the eggs of Taenia Sp, one respondent tested positive for the eggs of Ascaris lumbricoides. The result showed an increased risk of helminthiasis in the group with more than 35 years of work duration compared with those with 35 years or less. Fisher's Exact Test indicated a statistically significant association between work duration and helminthiasis.